Current Trends in Sustainability Education and the Future of Sustainability Education in Nigeria - Akinsemolu , Adenike A.; Arijeniwa , Foluke V. (Journal of Sustainable Development Law and Policy, 2025)
This article examines the current trends in sustainability education and the future of sustainability education in Nigeria. It contends that development and environment are intertwined and thus should be systematically embedded into educational activities to yield environmentally responsible and accountable policies and citizens in the quest for sustainable development. The significant roles of Environmental Education (EE) as a tool for propagating United Nations sustainable development goals (SDGs) have been identified within Nigeria’s national guidelines and policy visions. While there is this recognition, implementing and delivering EE programs remains significantly affected by various practical implementation challenges. Despite various studies documenting the value of EE for the achievement of the SDGs, challenges related to governance and laws limiting the roll-out of these programs in Nigeria continue to pose implementation challenges. Thus, this article seeks to look at the various institutional and legal challenges arising with the implementation of these programs within Nigeria and how to practically address them. The main challenges identified in this study are inadequate funding, capacity gaps, insufficient facilities, inadequate infrastructure, and the lack of EE in national strategies and plans. Recommendations for addressing these challenges are provided, along with conclusions on the future outlook.